The Use of Foreign Forces to Combat Terrorism at the Request of the Country Concerned - Fares, Zaid; Khaleel, Mahmood (Journal of Legal Sciences, 2022)
The escalating terrorist operations in the world clearly revealed that the international community still lacks a comprehensive strategy to win the war against terrorism, which has spread like cancer in many parts of the world, and has confused the expansion of the Islamic State in Iraq and the Levant "ISIS" in Iraq and Syria and its control over areas In the two countries, the political accounts of the various local, regional and international actors are broad, and with the failure of the local forces to confront that organization or limit its influence, the United States of America has had to return to military intervention in Iraq, especially after the organization executed American journalists, despite its sizes. On direct intervention in its crises since the completion of the withdrawal of its forces from it in late 2011, the American intervention was welcomed by most of the international and regional powers that participated with it in an international coalition, and presented itself as a basic partner in combating terrorism.